Model Pendekatan Manajemen Hubungan Masyarakat MA MINAT Kesugihan Dalam Meningkatkan Citra Lembaga - Abdul Gina Arrouf Muammarulloh; Umi Halwati (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
Public Relations is not a cartoon character with a shovel following an elephant in a circus parade. Although sometimes called upon to clean up the mess, effective public relations helps management avoid the mess in the first place (Smith, 2021). Human strategies built by humans can instill trust in the public not only to obtain a positive image. The type of research used in this study is a qualitative method with a descriptive approach. Sources of data collected in this study through interviews, observation, and documentation. While the research location was at MA MINAT in Kesugihan which is in Cilacap district. Public Relations MA MINAT Kesugihan has a very important role for the institution, both in the field of organization and other services. A publicist must be able to create a positive image for the institution so as to form a good public opinion as well. MA MINAT Kesugihan is in the midst of social life, the community will continue to interact and relate directly or indirectly with the surrounding community. In addition to short-term measures of Public Relations processes and results, Public Relations requires indicators and measurements that are useful for identifying, maintaining, and evaluating long-term relationships for scanning the public environment, successful strategies for maintaining relationships, and outcomes.